The making of another major motion picture masterpiece : a novel [compact disc, unabridged] - Hanks, Tom (Random House Audio, 2023)
Part One of this story takes place in 1947. A troubled soldier, returning from the war, meets his talented five-year-old nephew, leaves an indelible impression, and then disappears for twenty-three years. Cut to 1970: The nephew, now drawing underground comic books in Oakland, California, reconnects with his uncle and, remembering the comic book he saw when he was five, draws a new version with his uncle as a World War II fighting hero. Cut to the present day: A commercially successful director discovers the 1970 comic book and decides to turn it into a contemporary superhero movie. Cue the cast: We meet the film's extremely difficult male star, his wonderful leading lady, the eccentric writer/director, the producer, the gofer production assistant, and everyone else on both sides of the camera.